PELAKSANAAN PEMBERDAYAAN EKONOMI MASYARAKAT KAMPAR MELALUI LEMBAGA EKONOMI DESA DI DESA BATUSASAK KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR TAHUN 2010-2012 - Eprizal "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The goals of this research is to analyze and to describe how the Rural Economic Institute in a program of effort empowering people to be independent and prosperous society. In practice, it is not compatible with expectations and Operational Standards and Procedures, because the society has been too spoiled with the assistance pragmatically. Uncovering the weaknesses and constraints in the implementation of the Empowerment Program, this research tries to approach the implementation of government policies that are used to analyze the problems of who you really are instrumental in its implementation.Empowerment Program is a new format that provides opportunities for people to participate in determining things that can lift their lives. However, the success or failure of the implementation, depending on how the strategy and the involvement of society itself while also monitoring and supervision of the related circles. Based on the analysis, this research is describing that implementation of the Empowerment Program can be seen from the management and effectiveness of the program.Keywords : Policy , Empowerment , Democracy.